Estratégias analítico-comportamentais como base para atuação de professores na Educação Especial: uma revisão sistemática da literatura - Coelho, Flavia Simão Cavalcanti (2023)
The present study aimed to carry out a bibliographic survey of national articles on Applied Behavior Analysis and strategies for facilitating the teaching-learning process in Special Education from 2013 to 2022 as a theoretical and practical contribution to teachers, whether in specialized school or in Specialized Educational Care. The first stage, identification, consisted of searching the articles carried out in the databases of the Journal Portal of the Coordination for the Improvement of Higher Education Personnel (CAPES); Scientific Electronic Library Online (SciELO), and Virtual Health Library (BVS), and the PRISMA protocol (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) was chosen for the design of this review because it presents a set of guidelines for conducting systematic reviews and meta-analyses. Among the 28 studies selected, it was found, among other aspects, that most of the work was focused on teacher training; of the deficiencies and disorders most found in research, ASD is the most frequent; the most relevant strategies raised were the teaching of the basic principles of Behavior Analysis and differential reinforcement. This review indicated relevant contributions of analytical-behavioral strategies relevant to the performance of teachers in special education